Management of Madrasah Kulliyatul Muallimin Al-Islamiyyah Gontor in Enhancing Administrative and Academic Performance: An Analysis Based on Henry Fayol’s 14 Principles of Management - Kharis Syuhud Mujahada; Hanifah Noviandari; Nur Habib Bagas Budiawan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study explores the implementation of Henry Fayol’s 14 principles of management in the context of management at Madrasah Kulliyatul Muallimin Al-Islamiyyah (KMI) Gontor to enhance both administrative and academic performance. The central issue is how to adapt and apply classical management principles within the framework of modern Islamic education to achieve optimal organizational effectiveness. Employing a phenomenological approach with qualitative methods, the research involved in-depth interviews with school leaders, administrators, and educators at KMI Gontor. Data were collected through participatory observation, structured interviews, and analysis of institutional documents. The findings reveal that the application of Fayol’s 14 principles within KMI Gontor has successfully created an adaptive and effective management system, with several modifications aligned with Islamic values and the distinctive characteristics of pesantren education. The key findings indicate that the principles of division of work, unity of command, and esprit de corps serve as the main foundation for achieving structured administrative performance, while the principles of initiative and equity meaningfully contribute to improving academic quality. This study offers theoretical contributions to the development of Islamic education management models that integrate the traditional wisdom of pesantren with modern management theory, as well as practical implications for advancing management systems in contemporary Islamic educational institutions.